The Effect of COVID-19 on Tawjeihi Students' Anxiety and Depression in Jordan: A Cross-sectional Study - Azhar Ashami; Nihaya Al Sheyab (Jordan University of Science and Technology, 2023)
Background: The practicing of online learning by Tawjihi students left many experiencing different levels of anxiety and depression. Objective: The objective of this study is to investigate the level of anxiety and depression among the students who practiced online learning through COVID-19. Methodology: The study used convenience sampling method to collect data. The total number of sample reached 390 students. The students were selected from the University of Jordan and Applied Science University inside Amman. The other part of the sample was collected from the governmental and private schools in Amman governorate. The questionnaire was used as a tool for data collection. Results: The results showed a wide variation of the conditions inside households that left deep impact on the students in Tawjihi. The previous conditions and the difficulties the families faced to save the internet with high criteria left high pressure on Tawjihi students. The results showed in the complete lockdown due to COVID-19 experienced different levels of depression and anxiety. The results showed that the students were depressed from online learning due to the difficulties they faced to reach the online sessions and the difficulty to manage the online platforms. Conclusions and recommendations: Online learning left different levels of depression and anxiety among the Tawjihi students as a result of the low experience in online. The study recommended the preparation of students and guide them on how to utilize online learning with the minimization of depression and anxiety through continuous training.